Trust factors influencing the adoption of mobile commerce / Nur Haslinda Che Ahmad - Che Ahmad, Nur Haslinda (2017)
Nowadays, new technologies and communication channels arise constantly and lead to a new way of conducting a business. This situation will influence businesses to restructure the area of their business by using the new tools in order to adopt new markets or business trends. However, nowadays, consumers easily embrace all these new technologies and channels than in previous decades. Therefore, both businesses and consumers can take these advantages such as having more convenient, faster and safer if compared to the previous and traditional method of the transactions. In addition, currently millions of people use smartphones and tablets to access the Internet for entertainment, information and purchasing the services or products by using their smartphones. Hence, trust becomes the important of any kind of transaction because no proven guarantees that vendor will not engage in harmful opportunistic behaviors. Therefore, it is very in important to build trust among mobile commerce users to adopt this technology because it may affects intention among them to buy services or goods and also willing to provide their personal data through the mobile commerce application during the transactions process without any doubts. There are various problems that faced by the users regarding trust in mobile commerce has been identified in this research such as lack of trust, lack of confident, lack of knowledge and other mobile commerce issues related to technology. In this research, there are three objectives. The first objective is to identify problems faced by users in mobile commerce usage. Next is to identify trust factors influencing users to adopt mobile commerce technology that is the second objective while the third objective is to propose set of recommendation that may help user to adopt mobile commerce technology that involve monetary transaction. The model proposed in this research is 'Trust Model Influencing the Adoption of Mobile Commerce (PTMIAMC)' and this model used to identify trust factors influencing the adoption of mobile commerce among users in Klang Valley. This study focuses on 4 factors; perceived website characteristic, perceived ease of use, perceived useful and security towards trust in mobile commerce adoption. Data were collected using survey questionnaires that were carried out among 254 of mobile users in Klang Valley. All the accumulated data was processed using Statistical Package for the Social Science (SPSS). Pearson Correlation and ANOVA analysis were used to test the research questions. The findings provide evidence that perceived ease of use is the factor that influences user trust in mobile commerce adoption. The results also show that all of four factors have significant relationship towards users trust in mobile commerce adoption. Further research could be enhanced by expand the research with different trust factors to see the adoption of mobile commerce in Malaysia.